Innovation in the pandemic: the actions of the Federal University of Mato Grosso do Sul to guarantee the rights of the university community - de Carvalho, Leonardo Chaves; Solano, Leticia de Barros (Universitas Diponegoro, 2022)
The Federal University of Mato Grosso do Sul (UFMS), in order to meet the United Nations Sustainable Development Goals and guarantee the constitutional rights to health and higher education of its university students, adopted innovative initiatives during the Covid-19 pandemic, allowing the maintenance of academic and administrative activities. With the emergency remote teaching for students and home office for servers, emergency aid for digital inclusion was made available, such as costing internet packages, mobile data chip distribution, electronic equipment loan, financing of personal protective equipment and installation of internet via radio in villages for indigenous students. Professors were offered training courses on information and communication technology tools and innovative methodologies for remote teaching. Furthermore, UFMS offered free molecular testing and diagnosis of Sars-Cov-2 to members of the academic community of Cidade Universitária who presented symptoms of Covid-19. All these actions carried out by UFMS, besides highlighting it on the national scene, made it possible to complete the 2020 academic calendar within the same year, an achievement that took place only in two other Brazilian federal universities.Keyword: Innovation in the pandemic. Right to education. Right to health. Digital inclusion. Sustainable Development Goals